Analysis of the Leadership Style of the Intensive Care Unit Head Nurse on the Quality of Nursing Services at Grandmed Hospital Lubuk Pakam - Romi Syaputra Tarigan; Karnirius Harefa; Tati Murni Karo Karo (JURNAL KESMAS DAN GIZI (JKG), 2026)
Leadership is the process of directing and influencing individuals to enhance motivation in achieving organizational goals; therefore, the role of a leader is a crucial factor in determining the success of service quality. The head nurse of the Intensive Care Unit (ICU) has a strategic responsibility in improving the quality of nursing services through the implementation of various leadership styles, including democratic, authoritarian, laissez-faire, transactional, and transformational styles, as well as through supervisory functions as part of the actuating function to ensure that all programs are carried out effectively and efficiently. This study aimed to analyze the leadership style of the ICU head nurse and its relationship with the quality of nursing services at Grandmed Hospital Lubuk Pakam. This research employed a quantitative non-experimental design with a descriptive correlational approach and a cross-sectional method. The study was conducted at Grandmed Hospital Lubuk Pakam with a total population of 68 respondents, and the sampling technique used was non-probability sampling. The results showed a significant relationship between the leadership styles (democratic, authoritarian, laissez-faire, transactional, and transformational) of the ICU head nurse and the quality of nursing services. It can be concluded that each leadership style has its own strengths and weaknesses; however, the appropriate application of leadership style by the ICU head nurse contributes to improving the quality of nursing care provided to patients.